Ultrastretchable Elastic Shape Memory Fibers with Electrical Conductivity - Park, Sungjune; Baugh, Neil; Shah, Hardil K.; Parekh, Dishit P.; Joshipura, Ishan D.; Dickey, Michael D. (Advanced science, 2019)
Herein, elastomeric fibers that have shape memory properties due to the presence of a gallium core that can undergo phase transition from solid to liquid in response to mild heating are described. The gallium is injected into the core of a hollow fiber formed by melt processing. This approach provides a straightforward method to create shape memory properties from any hollow elastic fiber. Solidifying the core changes the effective fiber modulus from 4 to 1253 MPa. This increase in stiffness can preserve the fiber in a deformed shape. The elastic energy stored in the polymer shell during deformation drives the fiber to relax back to its original geometry upon melting the solid gallium core, allowing for shape memory. Although waxes are used previously for this purpose, the use of gallium is compelling because of its metallic electrical and thermal conductivity. In addition, the use of a rigid metallic core provides perfect fixity of the shape memory fiber. Notably, the use of gallium—with a melting point above room temperature but below body temperature—allows the user to melt and deform local regions of the fiber by hand and thereby tune the effective modulus and shape of the fiber. Herein, soft and ultrastretchable elastic shape memory fibers with electrical conductivity are demonstrated fabricated by injecting liquid metal, gallium, into the elastic and hollow fibers. The ability to change the core of the fiber from liquid to solid allows an enormous modulus change and thus, excellent shape memory effects.